Tough Talking: how to handle awkward situations - Martin, David (India : University Press, 1994)
Business
Keywords: Business; techniques; Manoeuvring warring; Tough Talking; Tough; talking; Terrors; good corporate citizen; nuisances; Managing Media; Customer Care; Awkward attitudes; performance Problems